Establishing a molecular toolbox of lineage-specific real-time RT-PCR assays for the characterization of foot-and-mouth disease viruses circulating in Asia - Saduakassova, Meruyert A.; Wood, Britta A.; Henry, Elisabeth; Gray, Ashley R.; Mioulet, Valérie; Sultanov, Akhmetzhan A.; Wadsworth, Jemma; Knowles, Nick J.; Di Nardo, Antonello; King, Donald P.; Bachanek-Bankowska, Katarzyna (Frontiers in Veterinary Science, 2023)
Foot-and-mouth disease (FMD) is endemic in many Asian countries, with outbreaks regularly occurring due to viruses from serotype O, A and Asia1 lineages that co-circulate in the region. The ability to rapidly characterise new virus occurrences provides critical information to understand the epidemiology and risks associated with field outbreaks, and aides with the selection of appropriate vaccines to control the disease. FMD lineage-specific characterisation is usually determined via sequencing; however, this capacity is not always readily available. Here we provide a panel of real-time RT-PCR (rRT-PCR) assays to allow differentiation of the FMD virus (FMDV) lineages known to be co-circulating in Asia during 2020. This panel included five new rRT-PCR assays designed to detect lineages O/ME-SA/PanAsia-PanAsia-2, O/ME-SA/Ind-2001, O/SEA/Mya-98, O/CATHAY and A/ASIA/Sea-97, plus three published rRT-PCR assays for A/ASIA/Iran-05, A/ASIA/G-VII and serotype Asia1. Samples of known FMD lineage (n=85) were tested in parallel with all eight lineage-specific assays, as well as an established 3D pan-FMD rRT-PCR assay. All samples (85/85) were assigned to the correct serotype, and the correct lineage was assigned for 70/85 samples where amplification only occurred using the homologous assay. For 13/85 of the samples, there was amplification in two assays; however, the correct lineage could be designated based on the strongest Ct values for 12/13 of these samples. An incorrect lineage was assigned for 3/85 samples. The amplification efficiencies for the five new RT-PCR assays ranged between 79.7 and 100.5%, with nucleic acid dilution experiments demonstrating broadly equivalent limits of detection when compared to the 3D pan-FMD rRT-PCR assay. These new tests, together with other published lineage-specific rRT-PCR assays, constitute a panel of assays (or molecular toolbox) that can be selected for use in FMD endemic countries (individually or a subset of the assays depending on region/lineages known to be circulating) for rapid characterisation of the FMDV lineages circulating in Asia at relatively low cost. This molecular toolbox will enhance the ability of national laboratories in endemic settings to accurately characterise circulating FMDV strains and facilitate the prompt implementation of control strategies, and may be particularly useful in settings where it is difficult to access sequencing capability.